Sustainable Development Literacy for Educators and Librarians - Rudić, Gordana; Brković, Mirjana; Pajić, Dejan (Journal of Integrated Information Management, 2024)
Purpose – This paper aims to present and analyse the experiences and challenges during the development of sustainable development literacy (SDL) implemented in the context of the EDUCABILITY project. Design/methodology/approach – It briefly discusses the methods and tools used to deliver a source mapping for SDL, a relevant Delphi Study, an SDL Curriculum and an e-Learning Module in the EDUCABILITY Virtual Learning Environment. Findings – The systematic review of international literature and the results of the Delphi Study enabled the proposal of an SDL curriculum, including definitions, key concepts and content, learning objectives and outcomes, teaching approaches and evaluation methods. Originality/value - The proposed educational materials enable the capacity of educators and librarians in SDL to apply it to different problems and various aspects of the same problem.